Family business and transaction exposure - Khalil Nimer; Mahmoud Nassar; Naser M. AbuGhazaleh; Abdulhadi Ramadan (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
This study provides additional evidence and insight into theories on transaction exposure as it empirically examines the magnitude of transaction exposure in Kuwait, a developing country. Specifically, it investigates factors that might influence Kuwaiti firms' responses to their transaction exposure and how being a family business or part of a family business group could play a mediating role in this response. Through conducting a questionnaire survey with the largest 147 industrial and commercial Kuwait firms, the results of a multinomial logistic regression indicate that theories on financial hedging seem to be inapplicable in the Kuwaiti case. However, these theories provide only partial explanations for management behavior in response to the transaction exposure of Kuwaiti companies. Findings show that a firm being part of a family business group is significantly correlated with its level of hedging, suggesting that firms that are members of a family group of businesses are expected to hedge at a higher level. This points to other theories, such as institutional theory, as playing greater roles in explaining the transaction exposure behaviors of firms in developing countries, and also suggests that family-controlled businesses are expected to engage in more innovative financial strategies and hedge at a higher level. The research findings imply that Kuwaiti firms need to be more aware of their transaction exposure and pay more attention to the related issues. Training programs in risk-management strategies should be provided to decision makers to help them evaluate the hedging strategies they employ. This study shows how different behaviors toward risk exist between firms that operate in developed and developing countries, including the effect of being part of a family business resulting in firms engaging in more innovative financial strategies when dealing with risk.
Keywords: D81; F31; 650; family business; financial derivatives; gulf countries; hedging; transaction exposure